Increased circulating microparticles in streptozotocin‐induced diabetes propagate inflammation contributing to microvascular dysfunction. (9th January 2019) - Feng, Qilong; Stork, Christian J.; Xu, Sulei; Yuan, Dong; Xia, Xinghai; LaPenna, Kyle B.; Guo, Ge; Sun, Haoyu; Xu, Li‐Chong; Siedlecki, Christopher A.; Brundage, Kathleen M.; Sheaffer, Nate; et al.
Abstract : Key points: Circulating microparticles (MPs) are elevated in many cardiovascular diseases and have been considered as biomarkers of disease prognosis; however, current knowledge of MP functions has been mainly derived from in vitro studies and their precise impact on vascular inflammation and disease progression remains obscure. Using a diabetic rat model, we identified a >130‐fold increase in MPs in plasma of diabetic rats compared to normal rats, the majority of which circulated as aggregates, expressing multiple cell markers and largely externalized phosphatidylserine; vascular images illustrate MP biogenesis and their manifestations in microvessels of diabetic rats. Using combined single microvessel perfusion and systemic cross‐transfusion approaches, we delineated how diabetic MPs propagate inflammation in the vasculature and transform normal microvessels into an inflammatory phenotype observed in the microvessels of diabetic rats. Our observations derived from animal studies resembling conditions in diabetic patients, providing a mechanistic insight into MP‐mediated pathogenesis of diabetes‐associated multi‐organ microvascular dysfunction. Abstract: In various cardiovascular diseases, microparticles (MPs), the membrane‐derived vesicles released during cell activation, are markedly increased in the circulation. These MPs have been recognized to play diverse roles in the regulation of cellular functions. However, current knowledge of MP function has been largely derived from in vitro studies. The precise impact of disease‐induced MPs on vascular inflammation and disease progression remains obscure. In this study we investigated the biogenesis, profile and functional roles of circulating MPs using a streptozotocin‐induced diabetic rat model with well‐characterized microvascular functions. Our study revealed a >130‐fold increase in MPs in the plasma of diabetic rats compared to normal rats. The majority of these MPs originate from platelets, leukocytes and endothelial cells (ECs), and circulate as aggregates. Diabetic MPs show greater externalized phosphatidylserine (PS) than normal MPs. When diabetic plasma or isolated diabetic MPs were perfused into normal microvessels or systemically transfused into normal rats, MPs immediately adhered to endothelium and subsequently mediated leukocyte adhesion. These microvessels then exhibited augmented permeability responses to inflammatory mediators, replicating the microvascular manifestations observed in diabetic rats. These effects were abrogated when MPs were removed from diabetic plasma or when diabetic MPs were pre‐coated with a lipid‐binding protein, annexin V, suggesting externalized PS to be key in mediating MP interactions with endothelium and leukocytes. Our study demonstrated that the elevated MPs in diabetic plasma are actively involved in the propagation of vascular inflammation through their adhesive surfaces, providing mechanistic insight into the pathogenesis of multi‐organ vascular dysfunction that commonly occurs in diabetic patients. Key points: Circulating microparticles (MPs) are elevated in many cardiovascular diseases and have been considered as biomarkers of disease prognosis; however, current knowledge of MP functions has been mainly derived from in vitro studies and their precise impact on vascular inflammation and disease progression remains obscure. Using a diabetic rat model, we identified a >130‐fold increase in MPs in plasma of diabetic rats compared to normal rats, the majority of which circulated as aggregates, expressing multiple cell markers and largely externalized phosphatidylserine; vascular images illustrate MP biogenesis and their manifestations in microvessels of diabetic rats. Using combined single microvessel perfusion and systemic cross‐transfusion approaches, we delineated how diabetic MPs propagate inflammation in the vasculature and transform normal microvessels into an inflammatory phenotype observed in the microvessels of diabetic rats. Our observations derived from animal studies resembling conditions in diabetic patients, providing a mechanistic insight into MP‐mediated pathogenesis of diabetes‐associated multi‐organ microvascular dysfunction.